REVITALIZATION OF STUDENT CHARACTER VALUES AT MA DARUL FALLAH UNISMUH BISSOLORO, BUNGAYA DISTRICT, GOWA REGENCY: REVITALISASI NILAI-NILAI KARAKTER SANTRI DI MA DARUL FALLAH UNISMUH BISSOLORO KECAMATAN BUNGAYA KABUPATEN GOWA - Heri Tahir; Bakhtiar; Saneru (SOSIOEDUKASI, 2026)
This study aims to analyze strategies for revitalizing the character values of santri at MA Darul Fallaah Unismuh Bissoloro in facing the challenges of moral degradation among the millennial generation and the influence of digitalization. Using a qualitative approach with a case study method, the research was conducted through participatory observation, in-depth interviews with 15 key informants (the head of the madrasah, teachers, and santri from grades X–XII), and documentation during the period of January–May 2025. The findings show that the revitalization of santri character is carried out through three main strategies: (1) integration of ta’dib (adab/ethics) values into all daily pesantren activities, (2) strengthening qiyadah (leadership) through Hizbul Wathan (HW) scouting programs and the Muhammadiyah Student Association (IPM), and (3) adaptation of technology-based learning methods controlled according to Islamic principles. Critical findings reveal tensions between traditional pesantren values and the digital culture of santri, which are addressed through a tawazun (balance) approach between the use of technology and the cultivation of akhlaq al-karimah (noble character). The study recommends the development of character modules based on maqashid sharia and strengthening the role of parents through weekly muhadharah programs as sustainable strategies for revitalizing santri character in the post-pandemic era. KEYWORDS Character revitalization, students, madrasah, modern Islamic boarding school, Islamic values